(untitled) (World Bulletin of Management and Law, 2023)
This study aimed to show the policy of the Central Bank of Iraq in managing banking liquidity and its impact on private banks, where private banks suffer from the absence of government interest in them, which caused the emergence of many problems between them and government banks on the one hand, and between them and the Ministry of Finance as a result of the prohibition of dealing with state institutions with private (private) banks . The study concluded that the existing problems in the relationship between government and private banks, and between the government and private banks led to the fragmentation of the banking market, and that the state limited its transactions to government banks only, and did not cooperate with private banks, which led to many negative effects, including weakening the banking market and making it work. In an incorrect way, as problems arose between Iraqi banks because all government departments refuse to receive checks issued by private banks, and even when one of these banks pays its tax, the check must be issued by the government-run Rafidain Bank .